Novel germline MLH1 and MSH2 mutations in latvian Lynch syndrome families - Berzina, D.; Irmejs, A.; Kalniete, D.; Borosenko, V.; Nakazawa-Miklasevica, M.; Ribenieks, K.; Trofimovics, G.; Gardovskis, J.; Miklasevics, E. (Experimental Oncology, 2012)
Background/Aims: Hereditary non-polyposis colorectal cancer or Lynch syndrome is an autosomal dominantly inherited disease with high penetrance, mostly due to mutations in the MLH1 and MSH2 genes. The aim of this study is to investigate the mutation spectrum of the MLH1 and MSH2 genes. Methodology: High risk colorectal cancer families were selected from overall 1053 consecutive patients. Screening of germline mutations in the MLH1 and MSH2 was performed by direct sequencing and multiplex ligation-dependent probe amplification. Results: Ten patients fulfilled the Amsterdam I/II criteria and Bethesda guidelines of the Lynch syndrome. Three novel mutations were identified in MLH1 and MSH2 genes, as well as two known mutations in the MLH1 gene. Large rearrangements in the MLH1 gene were found in two patients. Conclusions: The mutations in the MLH1 and MSH2 genes in Latvian high-risk families are highly heterogeneous. Combination of direct sequencing and MLPA is the most appropriate molecular method of detecting hereditary nonpolyposis colorectal cancer patients and family members at risk.